Peran Insentif dan Jaminan Sosial dalam Meningkatkan Prestasi Kerja Karyawan Pada PT. Gondari Media Pratama Padang - Lenny Hasan; M. Yusri Syah Putra; Liza Zulbahri (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
There are several factors that affect employees at work, so that it gives an impact on work performance generated by employees, while the factors in the form of incentives and social security provided by the company. This study aims to determine the effect of incentives and social security on the work performance of employees of PT. Gondari Media Pratama Padang partially or simultaneously. The research method used is quantitative. The sampling technique used is saturated sampling, so the sample is 60 respondents. Data analysis techniques used are multiple linear regression, t test, F test and coefficient of determination. Based on the partial test results found that incentives and social security have a positive and significant effect on the work performance of employees of PT. Gondari Media Pratama Padang because the significant value <alpha (α) = 0.05. The results of testing together found that incentives and social security have a positive and significant effect on the work performance of PT. Gondari Media Pratama Padang because the significant value <alpha (α) = 0.05. Based on the test results the coefficient of determination is known as Adjusted R-Square value of 0.480, meaning that the ability of the incentive variable (X1) and social security (X2) explains work performance by only 48% while the remaining 52% is explained by other variables not used in this study. Keywords: Incentives, Social Security and Job Performance.